Malaysian millenial voices - MALACHI EDWIN VETHAMANI (Maya Press Sdn. Bhd., 2021)
"After the relative drought during the years since Malaysia first took to the vocation of writing verse in English in the nineteen fifties. we now have in this collection of poems by Malaysia millennials signs of coming shower. By their numbers, they show more clearly than before their diversity in communal origins, gender, cultural interest, and regional spread. As Malaysians, they have arrived, making a home here for poetry in English. Gone is the angst of the poets who began publishing in the fifties and sixties over a perceived exilic condition, the proper language to write in, the country's cultural situation and the lack of literacy antecedents. The language in this collections, as may be expected, is very twenty-first century, a toned-down speech of conversation about ordinary things and everyday events in an urbanised environment. The collection marks on ongoing evolution of Malaysia poetry. I am optimistic that from the poets represented here, there will emerge at least two or three important voices in the decades ahead." -- Wong Phui Lam